Desenvolvimento de materiais dentários resinosos a partir do líquido da casca da castanha de caju - Moreira, Madiana Magalhães (2022)
Monomers have been synthesized to reduce the use of bisphenol A derivatives and to increase the mechanical properties of collagen and polymers in order to improve the biocompatibility and long-term performance of dental materials. A natural and renewable source of phenolic lipids is the cashew nut shell liquid (CNSL), which in its technical form is composed mainly of cardanol. Cardanol presents a variety of reactional sites, besides its flexible and hydrophobic molecular structure, favorable for the development of methacrylic monomers. Thus, this thesis consists of three chapters, which aim, respectively, to: 1) synthesize methacrylic monomers obtained from the incorporation of methacrylate groups in the carbon chain of cardanol, which may also be added to the phenolic hydroxyl, for application in dental materials; 2) evaluate the effects on matrix metalloproteinases (MMPs) inhibition, physicochemical properties and dentin adhesion of the incorporation in universal adhesive of cardanol methacrylate; 3) analyze the influence on physicochemical and mechanical properties of composite resins of the replacement of Bis-GMA by a cardanol-derived trimethacrylate. Monomers cardanol methacrylate (CNMA) and cardanol trimethacrylate (CTMA) were synthesized and characterized using nuclear magnetic resonance and Fourier transform infrared spectroscopy (FT-IR). In chapter 2, the following collagen crosslinkers were added in 2 wt % to the Ybond Universal® adhesive (control): proanthocyanidin, cardanol and CNMA. Inhibition MMPs was evaluated by zymography, the degree of conversion was assessed by FT-IR, water sorption and solubility, and dentin adhesion by microtensile bond strength and nanoleakage tests by scanning electron microscopy after 24 hours and 6-month aging. Data were analyzed by ANOVA and Tukey's post-test (α=0.05). CNMA was effective in inhibiting MMPs and reducing solubility without interfering with adhesive polymerization; however, it could not promote less degradation of the adhesive interface in long-term. In chapter 3, composite resins were formulated (50 wt % Bis- GMA + 50 wt % TEGDMA), and the effect of CTMA incorporation was investigated by means of degree of conversion by FT-IR, water sorption and solubility, viscosity, thermal degradation, and mechanical properties were evaluated. Data were analyzed by ANOVA and Tukey's post- test (α=0.05). CTMA and control resins did not show significant differences regarding degree of conversion and mechanical properties (p>0.05); however, the incorporation of the trimethacrylate was effective in reducing viscosity, water sorption and solubility when compared to Bis-GMA resins (p<0.05). CTMA is a feasible co-monomer for dental restorative materials, as a Bis-GMA substitute, since it did not interfere in the chemical and mechanical properties and further improved the physical properties of the resins.